Role of Community Fish refuge in improving resilience food system - Sithirith, Mak; Sok, Sao; Sean, Vichet; Tuy, Sinak; Phay, Sokcheng; Ignowski, Elizabeth (WorldFish, 2024)
The role of Community Fish refuge (CFR) in improving fishery and food for local communities to address the climate change, particularly the role of woman who is involved in Community Fish refuge (CFR) conservation and intervention activities.